Faktor Faktor yang Mempengaruhi Terjadinya Low Back Pain Myogenic pada Tenaga Kependidikan di Universitas Katolik De La Salle Manado - Angelina Linda Poluan; Josef Sem Berth Tuda; Odi Roni Pinontoan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
One of the health problems that the office workers frequently face is called low back pain myogenic. Which one of its primary symptoms that may happen to a person is feeling pain in their lower back. The pain that is being felt may be caused a wrong working position for a long period of time. The focus of this study is to analyze the causes that lead to the growth of myogenic low back pain among the staffs at the Catholic University of De La Salle Manado. The applied method of this research is quantitative method using a cross sectional study. There were 60 people as the samples or participants who matched the inclusion criteria. The data were analyzed using univariat, bivariate, and multivariate. The results of the chi square analysis showed that the variables have an impact on low back pain myogenic with p < 0.05 were age (p = 0.025), the body mass index (p = 0.047), working hours (p = 0.037), work position (p = 0.000), and screen time duration (p = 0.012). In contrast, the variables that doesn’t have any relationship to myogenic low back pain was the gender (p = 0.528). The further research was conducted using the logistic regression which showed that the factor that had the biggest impact, was the employee’s age, the body mass index, work position and screen time duration. It is highly recommended to the staffs to work with ergonomic positions to avoid the low back pain myogenic.